Crosslinked poly(vinyl alcohol) hydrogel microspheres containing dispersed fenofibrate nanocrystals as an oral sustained delivery system. (April 2018) - Li, Tao; Lei, Yun; Guo, Miao; Yan, Husheng
Graphical abstract: Highlights: Fenofibrate nanocrystals dispersed in cross-linked hydrogel as oral formulation. The formulation shows high in vitro dissolution rate and sustained release. The formulation shows high in vivo bioavailability and sustained release behavior. Abstract: Poorly water soluble drugs often show low oral bioavailability due to their low dissolution rate. In the present study, cross-linked poly(vinyl alcohol) hydrogel microspheres were prepared. Nanocrystals of fenofibrate as a model of poorly water soluble drugs were dispersed within the poly(vinyl alcohol) hydrogel microspheres by swelling the microspheres with fenofibrate/methanol solution, followed by evaporation of the solvent methanol. The fenofibrate dissolution rate from the fenofibrate-loaded hydrogel microspheres in a medium simulating gastrointestinal tract conditions was much higher than the dissolution rate of free fenofibrate. And the dissolution assay also showed that fenofibrate released from the hydrogel in a sustained manner. In vivo pharmacokinetic study showed that the fenofibrate-loaded hydrogel microspheres showed much higher bioavailability compared with free fenofibrate, and similar bioavailability but longer half-lives and mean residence time and lower maximum plasma concentration compared with a marked fenofibrate formulation Lipanthyl® after oral administration in rats, indicating that the fenofibrate-loaded PVA hydrogel exhibited lower fluctuation in plasma drug concentration and more sustained release behavior.